2021
DOI: 10.1177/13567667211030675
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the effectiveness of emotional and rational user-generated contents in digital tourism platforms

Abstract: User-generated content (UGC) is one of the most important notions that influences tourists’ decision-making. However, the nature of UGC is still underexplored in the literature. The present study aimed to examine the impact of two different forms of UGC (i.e., emotional and rational) on tourists’ perceived values and their subsequent behavioural responses. Using the stimulus-organism-response (SOR) model, the two forms of UGC were conceptualised as informational stimuli, while tourists’ overall value assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 94 publications
0
40
0
Order By: Relevance
“…Second, PLS-SEM is suitable when predicting key target constructs in a research model (Chin et al , 2020). Third, PLS-SEM has been used in previous studies on environmentalism to perform data analysis and is suitable for exploratory research with a combination of explanatory and predictive methods (Cheung et al , 2021; Wut et al , 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, PLS-SEM is suitable when predicting key target constructs in a research model (Chin et al , 2020). Third, PLS-SEM has been used in previous studies on environmentalism to perform data analysis and is suitable for exploratory research with a combination of explanatory and predictive methods (Cheung et al , 2021; Wut et al , 2020).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, each value is independent and makes a unique contribution to each given choice (van Boerdonk et al , 2021). The concept has been empirically tested in different contexts, such as social media brand pages (Kim et al , 2011; Shi et al , 2016), tourism (Cheung et al , 2021; Sharma and Nayak, 2019) and environmental consumption (Bu et al , 2020; Yu et al , 2021; Garg et al , 2021). Thus, the present study uses CVT to explore the role of young people’s perceived values in establishing their pro-environmental attitudes and intentions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The studies analyzed emphasize the combination of areas such as customer engagement, customer participation and user-generated content . The study by Cheung et al (2021) contributes to the tourism marketing literature by empirically examining the impacts of two forms of user-generated content on tourists’ perceived values and their behavioral responses. Many studies have been conducted on user behavior’s influencing factors in virtual communities (such as co-creation and participants’ value-in-use).…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Information interactions showed the largest effect size for the mutual trust level of Karrot users. Cheung et al [ 67 ] discovered that emotional and information interactions are important drivers of consumers’ perceived value based on the SOR framework. Another prior study identified that interactions between consumers have an impact on evoking emotional attachment and behavioral intentions grounded on service-dominant logic [ 58 ].…”
Section: Discussionmentioning
confidence: 99%